Search equilibrium, production parameters and social returns to education: theory and estimation - Christian Holzner; Andrey Launov (Institute for the Study of Labor (IZA), 2005)
We introduce different skill groups and production functions into the Burdett-Mortensen equilibrium search model. Supermodularity in the production process leads to a positive intrafirm wage correlation between skill groups. Theory implies that increasing returns to scale can lead to a unimodal earnings density with a decreasing right tail even in the absence of productivity dispersion. Our empirical results indicate economy-wide increasing returns to scale. We use the structural estimates of the production parameters to investigate whether private returns to education equal social returns. Our estimates suggest a positive welfare effect from increasing the share of medium-skilled agents in the workforce.
Keywords: J21; J23; J64; 330; search; wage correlation; social returns to education